A scoping review on outcomes, interventions and cuff parameters for blood flow restriction training in the treatment of knee osteoarthritis - Gurjant Singh; Monika Hariramani; Saumya Kothiyal (Advances in Rehabilitation)
The most common type of arthritis that alters a joint's mechanical and structural properties is osteoarthritis (OA). Resistance training combined with blood flow restriction training (BFRT) is one of the new and promising non-pharmacological strategies for treating OA that has received attention recently. This paper aims to identify the outcomes and outcome measures used for BFRT in knee OA, evaluating BFRT intervention and cuff parameters. The Preferred Reporting Items for Systematic Reviews and Meta-analysis Extension for Scoping Reviews is followed while reporting on scoping reviews. The Cochrane Central Register of Controlled Trials, the Physiotherapy Evidence Database, and PubMed were among the databases that were searched for research. Eight studies were included. The range of outcomes used in the study were knee pain, function, strength, quadriceps cross-sectional area, quality of life, disease severity, growth hormone level, and Range of motion. The parameters that were used in the included studies ranged from 4-5 sets of 10-15 repetitions at 20%–30% of 1RM load; progressive blood restriction ranging from 30%–80% of arterial occlusion pressure occurred with placement of the cuff at the most proximal part of the thigh. Low-intensity exercise training combined with blood flow restriction (BFR) used with appropriate parameters is a viable alternative to traditional strategies for improving knee OA patients' pain, strength, muscle mass, hormones, functionality, range of motion, and overall quality of life.